Peripheral and central alterations affecting spinal nociceptive processing and pain at adulthood in rats exposed to neonatal maternal deprivation. (29th June 2016) - Juif, Pierre‐Eric; Salio, Chiara; Zell, Vivien; Melchior, Meggane; Lacaud, Adrien; Petit‐Demouliere, Nathalie; Ferrini, Francesco; Darbon, Pascal; Hanesch, Ulrike; Anton, Fernand; Merighi, Adalberto; Lelièvre, Vincent; et al.
Abstract: The nociceptive system of rodents is not fully developed and functional at birth. Specifically, C fibers transmitting peripheral nociceptive information establish synaptic connections in the spinal cord already during the embryonic period that only become fully functional after birth. Here, we studied the consequences of neonatal maternal deprivation (NMD, 3 h/day, P2–P12) on the functional establishment of C fiber‐mediated neurotransmission in spinal cord and of pain‐related behavior. In vivo recording revealed that C fiber‐mediated excitation of spinal cord neurons could be observed at P14 only in control but not in NMD rats. NMD was associated with a strong alteration in the expression of growth factors controlling C nociceptor maturation as well as two‐pore domain K+ channels known to set nociceptive thresholds. In good agreement, C‐type sensory neurons from NMD animals appeared to be hypoexcitable but functionally connected to spinal neurons, especially those expressing TRPV1 receptors. In vivo and in vitro recordings of lamina II spinal neurons at P14 revealed that the NMD‐related lack of C fiber‐evoked responses resulted from an inhibitory barrage in the spinal cord dorsal horn. Eventually, C‐type sensory‐spinal processing could be recovered after a delay of about 10 days in NMD animals. However, animals remained hypersensitive to noxious stimulus up to P100 and this might be due to an excessive expression of Nav1.8 transcripts in DRG neurons. Together, our data provide evidence for a deleterious impact of perinatal stress exposure on the maturation of the sensory‐spinal nociceptive system that may contribute to the nociceptive hypersensitivity in early adulthood. Abstract : Noxious events occurring early after birth are now well recognize to give rise to hyperexcitable circuits in the nociceptive system at later age. Here, we show that neonatal maternal deprivation (NMD) in rats produces a similar consequence: young adult animals exhibit low nociceptive thresholds and hyperexcitable C‐type nociceptors displaying high levels of Nav1.8 gene transcripts. Interestingly, NMD‐associated hypernociceptive state is preceded an alteration in the establishment of C‐type sensorispinal transmission which is characterized by (i) impaired expression of NGF and DGNF, (ii) hypoexcitable C‐type sensory neurons due to excessive K2P channel expression, and (iii) increased inhibition in the superficial layers of the spinal cord.